A clustering approach to solve the multiple travelling salesmen problem. (15th May 2006) - Chandran, Nishanth; Narendran, T.T.; Ganesh, K.
The multiple travelling salesmen problem (mTSP) involves scheduling m salespersons to visit a set of n nodes so that each node is visited exactly once while minimising the total distance travelled by the salespersons. The mTSP is a harder variant of the well-known travelling salesperson problem (TSP). A less-addressed criterion is the balancing of workloads amongst salespersons. In a departure from other methodologies that have been employed for this purpose, we propose a clustering approach to solve the mTSP. When tested over a range of data-sets, the proposed method is found to achieve a good balance of workloads among the clusters, each of which is visited by a salesperson.